ANALISIS FENOMENA MINUMA KERAS PADA ACARA HAJATAN PERNIKAHAN MASYARAKAT ( STUDI SOSIAL KEWARGANEGARAAN DESA GAPURA SUCI KABUPATEN BUNGO) - Nopriansyah, Deni; Dewi, Nurmalia; Aditya Candra, Alif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine and analyze the phenomenon of alcohol consumption during wedding celebrations in Gapura Suci Village, Bungo Regency, within the framework of civic social studies. It employs a qualitative approach, specifically phenomenology. Data were collected through passive participant observation, structured interviews, and documentation involving key, primary, and supplementary informants. The findings indicate that alcohol consumption has evolved into a social reality and a collective phenomenon integrated with nighttime entertainment activities. Analyzed through Emile Durkheim’s perspective, this practice manifests as a social fact driven by mechanical social solidarity and peer pressure; consequently, it has undergone social normalization (anomie), despite undermining residents' legal consciousness and violating local regulations. The study recommends strengthening community-based civic education to restore civic virtue and social order.